Growth mechanism of carbonated tricalcium silicate (C3S) under the high concentration of CO2: A novel research for CCUS wells - Lian, Jihong; Wu, Zhiqiang; Lei, Yu; Gao, Qiang; Mei, Kaiyuan; Cai, Jingxuan; Cheng, Xiaowei (Frontiers in Materials, 2022)
Under the engineering background of the carbon dioxide capture and geological storage technology (CCUS) cementing project, an experiment on the generation of cement single-phase tricalcium silicate CO2 carbonization products were carried out. Combining the phase diffraction pattern data and the thermogravimetric experiment, a relative crystallinity algorithm is proposed, which combines the quantitative results of the carbonized products with the relative crystallinity (RCP) results of each component. The growth and development mechanism of tricalcium silicate carbide crystal products under high temperature, high pressure and high concentration CO2 environment is deduced. The experimental results show that under the conditions of early gas phase carbonization, the carbonization rate of C3S first increases and then decreases as the carbonized crystal product grows. Under the conditions of early liquid phase carbonization, the carbonization rate of C3S first decreases and then increases with the generation and fragmentation of the hydration barrier layer. It provides a research basis and a new perspective for the subsequent analysis of the changes in the microstructure of the cement paste in the carbonization process under the CCUS engineering background.